2017
DOI: 10.1038/ncomms15811
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation recovery in tidal marshes reveals critical slowing down under increased inundation

Abstract: A declining rate of recovery following disturbance has been proposed as an important early warning for impending tipping points in complex systems. Despite extensive theoretical and laboratory studies, this ‘critical slowing down' remains largely untested in the complex settings of real-world ecosystems. Here, we provide both observational and experimental support of critical slowing down along natural stress gradients in tidal marsh ecosystems. Time series of aerial images of European marsh development reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
121
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 38 publications
7
121
1
Order By: Relevance
“…While there are many studies addressing temporal early warning signals, research into spatial indicators is far behind, with field experiments even more rare (Cline et al 2014, Scheffer et al 2015. Our results are consistent with recent experimental studies on spatial EWS showing that direct (e.g., recovery length) and indirect signatures of ecosystem fragility (classical spatial EWS in our study) may successfully forewarn the approach to a critical threshold (Cline et al 2014, Butitta et al 2017, Rindi et al 2017, van Belzen et al 2017. Our results are consistent with recent experimental studies on spatial EWS showing that direct (e.g., recovery length) and indirect signatures of ecosystem fragility (classical spatial EWS in our study) may successfully forewarn the approach to a critical threshold (Cline et al 2014, Butitta et al 2017, Rindi et al 2017, van Belzen et al 2017.…”
Section: Discussionsupporting
confidence: 89%
“…While there are many studies addressing temporal early warning signals, research into spatial indicators is far behind, with field experiments even more rare (Cline et al 2014, Scheffer et al 2015. Our results are consistent with recent experimental studies on spatial EWS showing that direct (e.g., recovery length) and indirect signatures of ecosystem fragility (classical spatial EWS in our study) may successfully forewarn the approach to a critical threshold (Cline et al 2014, Butitta et al 2017, Rindi et al 2017, van Belzen et al 2017. Our results are consistent with recent experimental studies on spatial EWS showing that direct (e.g., recovery length) and indirect signatures of ecosystem fragility (classical spatial EWS in our study) may successfully forewarn the approach to a critical threshold (Cline et al 2014, Butitta et al 2017, Rindi et al 2017, van Belzen et al 2017.…”
Section: Discussionsupporting
confidence: 89%
“…While the abiotic properties alone could be used to predict locations where salt marshes will establish, this ignores the feedback between the salt marsh and abiotic stressors, that is, the eco‐engineering effects. Recent research conducted in the Western Scheldt estuary, the Netherlands, showed that the border between the high biomass high marsh and low biomass pioneers zone can be found at a relative inundation period of around 0.45, which was shown to be applicable to Dutch as well as to North American salt marshes (Van Belzen et al, ). This empirical threshold is the result not only of the individual plant properties but also of the modifications of the abiotic conditions by the salt marsh.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, a marsh can recover from a dieback (Ogburn and Alber, 2006;Angelini and Silliman, 2012;Altieri et al, 2013). However, diebacks can also be permanent, especially if the marsh experiences erosion (Lottig and Fox, 2007;Silliman et al, 2012), such that the marsh elevation becomes too low for vegetation to grow (Wang and Temmerman, 2013;van Belzen et al, 2017). However, diebacks can also be permanent, especially if the marsh experiences erosion (Lottig and Fox, 2007;Silliman et al, 2012), such that the marsh elevation becomes too low for vegetation to grow (Wang and Temmerman, 2013;van Belzen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%